Interactive Spider Maps for Public Transportation - Francisco Miguel Amaro Maciel (2016)
In Public Transportation systems, accurate and good representation of information has been key to aid the customer on how to take more advantage of the service, to fulfil his travel needs. The Spider Map is a particular schematic representation to illustrate all travel possibilities from a given geographical location, stretching out in different directions without disregarding their geographic constraints. This work's goal is to research on the ways which a Spider Map can be made interactive, while still giving the user the information he needs, through a mobile touch application. Recently the map generation process automation has been studied, while satisfying the schematic design constraints. This generation process is only for the schematic map surrounding the geographic map, which has to be inserted manually, along with other graphical decisions. As such, this process is not finished and is only partly automated as a guideline for the drawing out the complete map. There are different possibilities to explore in technological approach from an interaction point of view, exploring different touch gestures. The current maps focus solely on the spatial context and disregard the interactive dynamic potential that a real time generation has access to, adding spatial and temporal information to represent information differently,challenging the existing representation standards concerning information representation. To optimize the research project, a mixed approach including development and user testing is proposed. Given the complexity of the algorithm used to generate a near perfect schematic map, it could be replaced by a simpler alternative, that is still able to represent the network accurately. This process also needs validation from Human-Computer interaction testing to make important design decisions, considering the new potential in technology and interface representation. The usage of touch interfaces is analysed, taking into consideration the technology usage and gestures. The real time generation point of view is taken into account, given that the possibility of caching pre-processed maps can impact the generation speed. This process starts with analysing state of the art revision, prototyping, and identifying a set of guidelines from an interaction point of view, followed by the development of a real web application that works in the city of Porto, using Public Transportation data.